20. Diffusion MRI and ADC accuracy at the isocenter: An AIFM multisite comparison study. (December 2018) - Coniglio, A.; Fedeli, L.; Belli, G.; Ciccarone, A.; Esposito, M.; Giannelli, M.; Gobbi, G.; Gori, C.; Mazzoni, L.N.; Nocetti, L.; Sghedoni, R.; Tarducci, R.; et al.
Abstract : Purpose: The AIFM working group on MR intercomparison has proposed a quality assurance protocol for MRI diffusion weighted imaging (DWI). The aim of this study is to test the accuracy of apparent diffusion coefficient (ADC) evaluation at the isocentre of the scanner. Methods: Seventeen centres and twenty-six MRI scanners (20/6; 1.5 T/3.0 T) were enrolled in this study. A custom spherical water phantom (14 cm diameter, filled with doped aqueous solution) specifically designed for DWI QA was provided to all participants. ADC value was certified as in[1] . Phantom was placed at isocentre of scanner. 5 mm thick axial slices at the isocentre were acquired, using three DWI sequences (b-value varying form 0 s/mm 2 to 1000 s/mm 2 at 200 s/mm 2 steps), differing in gradient diffusion direction. For each diffusion direction, ADC image was generated with monoexponential fit and corrected for temperature. Analysis was performed with a custom Matlab software code. Average ADC was calculated for each diffusion direction ( ADC x, ADC y, ADC z ) in a 2 × 2 cm 2 ROI at the centre of the phantom. A chi-squared consistency test was performed on the three ADC values. The mean value ( ADC ref ) was compared with the certified ADC C value. Results: Differences within ADC x, y, z are less than 1.5%, for 21 scanners. For seven scanners ADC x, y, z were not consistent among themselves. ( ADC ref / ADC C - 1 ) vary from +10% to −7% (mean value −1%). Only in four scanners | ( ADC ref / ADC C - 1 ) | is larger than 5%. Conclusions: The proposed protocol and multipurpose phantom provide a simple ADC quality assurance procedure. The measured isocentre ADCs are within 1% with reference to wrt diffusion directions and consistent with certified value within 1%.